THE INFLUENCE OF ACADEMIC PROGRESS IN UNDERGRADUATE COURSES ON THE CONSUMPTION OF ULTRA-PROCESSED FOODS AMONG NUTRITION STUDENTS - Silva Barros, Acacio; Helena de Souza Queiroz, Camila (Health and Society, 2025)
This study investigated the relationship between academic progress in undergraduate Nutrition courses and the consumption of ultra-processed foods among students. Although it is expected that the acquired knowledge will reduce this consumption, factors such as stress, high workload, and limited access to fresh foods can perpetuate it. Thus, we sought to analyze how these factors influence the diet of university students throughout the course. The research, of a descriptive and qualitative-quantitative nature, was carried out with 1,093 Nutrition students from Brazil, distributed between the 1st and 8th semesters. Data collection occurred via an electronic form containing demographic and eating habits questions, including frequency of consumption of carbohydrates, coffee, and sweetened beverages. Participants were selected through invitations in academic networks, and only those who accepted the Free and Informed Consent Form participated. The results indicated a trend of greater consumption of ultra-processed foods in the first semesters, with a gradual reduction throughout the course, suggesting that academic training may favor more judicious food choices. However, an increase in sporadic consumption was observed and a small portion of students maintained frequent consumption, exposing themselves to nutritional risks. Factors such as advertising, socioeconomic profile and adaptation to the academic routine influenced eating patterns. It is concluded that, despite the positive impact of nutritional education, structural and behavioral challenges still hinder the adoption of healthy eating habits.